Development of learning model based on sensory integration for students experiencing learning disabilities age 7–8 years - Aziz, Abdul; Jamaris, Martini; Sumadi, Tjipto (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2022)
This study aims to develop a learning model, based on sensory integration, for improving academic abilities in low-grade elementary school students, aged 7-8 years experiencing learning disabilities. This intervention is known to be an effective learning model for students experiencing learning impairments. The methodology included a mixed design with research and development techniques, as well as Martini Jamaris’s Model. The subjects were 400 students of an elementary school in DKI Jakarta. The results showed that the learning model using interventions based on sensory integration is more effective than the conventional type, which is used in reducing sensation hypersensitivity and hyposensitivity to an adaptive response. All students with learning disabilities who received an intervention based on sensory integration are 100% progressed in acquiring better academic skills and more adaptive.